VD_FINDINFO Décision / 2022 / 611 vom 8. August 2022 - VD Tribunal cantonal (2022)
ADMINISTRATION DES PREUVES, DÉFENSE OBLIGATOIRE, ADMISSION PARTIELLE | 134 CP, 130 let. b CPP (CH), 131 al. 3 CPP (CH), 131 CPP (CH), 141 CPP (CH), 309 CPP (CH)